The Influence of Trust, Technology Understanding, and Interconnected Network on the Digital Banking Services Usage in Pujiharjo Village, Tirtoyudo Subdistrict - Hartomy Akbar Basory; Sahala Manalu; Dhella Ayu Saputri (PT FORMOSA CENDEKIA GLOBAL, 2023)
Digital banking is a medium for customers to facilitate transaction activities. Through this, there are several variables that can affect the use of digital banking, namely trust, technology understanding, and interconnected networking. The aim of this study is to find out how confidence, technology understanding, and interconnected networking influence the use of digital banking services. The population and samples in this study were the Pujiharjo rural community, where the sample used a non-probability sample with a type of purposive sampling compared to 81 respondents through the spread of the questionnaire. The classic assumption test tools on SPSS used in this study are normality, homocadasthesity, non-multicolinerity, and linearity. The study concluded that the trust variables, the technology understanding, and the interconnected network have a positive impact on the use of digital banking.